I
icus
Guest
Hi, I'm studing the bootstrapped emitter follower amplifier, but I don't
understand how Zi is given by Zi = Rboot/( 1 - A ), where A is the gain.
In my book the explanation of this formula is this:
An input wiggle of vin result in an emitter wiggle ve +-= vi ( sorry for
the +-= I don't know how to write that the two quantity aren't perfectly
equal
).
So i = (vin - ve )/Rboot +-= 0, i.e Zin = vin/Iin = infinity.
Why in this analysis ib ( the current that through the transistor ) is
omitted?
Thank for your help!
understand how Zi is given by Zi = Rboot/( 1 - A ), where A is the gain.
In my book the explanation of this formula is this:
An input wiggle of vin result in an emitter wiggle ve +-= vi ( sorry for
the +-= I don't know how to write that the two quantity aren't perfectly
equal
So i = (vin - ve )/Rboot +-= 0, i.e Zin = vin/Iin = infinity.
Why in this analysis ib ( the current that through the transistor ) is
omitted?
Thank for your help!